Expertise docente Teorie, modelli didattici e strumenti innovativi - TOTO, Giusi Antonia (Media e tecnologie per la didattica - Open Access, 2019)
The main points of reflection posed by the volume concern the identity and role of the teachers in the digital society: teacher training, educational planning and the praxic effects of new media. The text proposes reflections on current issues, such as assessment - intended as a training process of knowledge acquisition - and innovative applications of academic research to new learning needs. The purpose of this contribution is to link constructs and paradigms to identify what makes a teacher highly qualified, from an eminently pedagogical point of view.